Epigenetics and energetics in ventral hippocampus mediate rapid antidepressant action: Implications for treatment resistance - Bigio, Benedetta; Mathé, Aleksander A.; Sousa, Vasco C.; Zelli, Danielle; Svenningsson, Per; McEwen, Bruce S.; Nasca, Carla (Proceedings of the National Academy of Sciences - PNAS, 2016)
Although regulation of energy metabolism has been linked with multiple disorders, its role in depression and responsiveness to antidepressants is less known. We found that an epigenetic and energetic agent, acetyl-L-carnitine (LAC, oral administration), rapidly rescued the depressive- and central and systemic metabolic-like phenotype of LAC-deficient Flinders Sensitive Line rats (FSL). After acute stress during LAC treatment, a subset of FSL continued to respond to LAC (rFSL), whereas the other subset did not (nrFSL). RNA sequencing of the ventral dentate gyrus, a mood-regulatory region, identified metabolic factors as key markers predisposing to depression (insulin receptors Insr, glucose transporters Glut-4 and Glut-12, and the regulator of appetite Cartpt) and to LAC responsiveness (leptin receptors Lepr, metabotropic glutamate receptors-2 mGlu2, neuropeptide-Y NPY, and mineralocorticoid receptors MR). Furthermore, we found that stress-induced treatment resistance in nrFSL shows a new gene profile, including the metabolic regulator factors elongation of long chain fatty acids 7 (Elovl7) and cytochrome B5 reductase 2 (Cyb5r2) and the synaptic regulator NPAS4. Finally, while improving central energy regulation and exerting rapid antidepressant-like effects, LAC corrected a systemic hyperinsulinemia and hyperglicemia in rFSL and failed to do that in nrFSL. These findings establish CNS energy regulation as a factor to be considered for the development of better therapeutics. Agents such as LAC that regulate metabolic factors and reduce glutamate overflow could rapidly ameliorate depression and could also be considered for treatment of insulin resistance in depressed subjects. The approach here serves as a model for identifying markers and underlying mechanisms of predisposition to diseases and treatment responsiveness that may be useful in translation to human behavior and psychopathology.